Central city revitalization with specific reference to redevelopment, transportation and pedestrian improvements - Erasmus, George-Chatwind (Stellenbosch : Stellenbosch University, 2012)
Study project (M. in Town and Regional Planning) -- University of Stellenbosch, 1992.